Hubungan Penerapan Program K3 dan Dukungan Rekan Kerja Terhadap Penggunaan APD pada Pekerja Proyek 6 Ruas Tol Dalam Kota KSO JAYA-ADHI Tahun 2021 - Bonaldi Sinurat, (2021)
The use of PPE is an effort to minimize losses due to the impact of accidents, although in the hierarchy of control OHS is included as a last resort, but PPE is effectively used to control the risks that still exist. Factors that affect compliance with the use of PPE in workers are age, OHS program , and support of co-workers. This study aims to determine the relationship between of age, Occupational Health and Safety (OHS) program, and support from co-workers for compliance with the use of PPE for workers in the Construction Project of 6 Inner-City Toll Roads KSO JAYA-ADHI in 2021. This research was a quantitative-analytic study. The population in this study was 150 workers. No more than 120 workers were recruited as samples by using an accidental sampling technique. This research was conducted from May until June 2021. Data were analyzed by using a Chi-square test. It has been found that 62 of 120 workers (51,7%) showed a high level of compliance to PPE use. The results of the analysis on statistical tests showed that safety talk (P-value = 0.001), safety sign (P-value = 0.000), safety patrol (P-value = 0.019), support from colleagues (P-value = 0.001) had significant relationship to compliance with the use of PPE. Age (P-value = 0,265) has no relationship to compliance with PPE use. Therefore, the company needs to consistently runs the OHS program and improve the quality of the OHS program so that workers comply with the use of complete PPE when working.